Influências do ser filha no ser mãe: um estudo psicanalítico sobre o processo de tornar-se mãe - Pereira, Rafaela (2024)
This dissertation aims to study the psychic processes involved in the construction of motherhood as experienced by women when becoming mothers, from a psychoanalytic perspective. The concepts of Psychic Transparence and Primary Maternal Preoccupation, developed respectively by Monique Bydlowski (2001) and Donald Winnicott (1956), were employed to understand the new female psychic functioning resulting from the transition to parenthood. This is a qualitative study conducted using psychoanalytic methodology. Through a theoretical-clinical approach and based on the narratives of a new mother, the research sought to investigate and discuss the psychic phenomena experienced and observed during the process of becoming a mother. The clinical material for the study was derived from six interviews conducted with the participant Maria. The interviews were recorded, transcribed, and analyzed using procedures typical of psychoanalytic practice: free listening, text clipping, and reconstruction. The original material was subjected to a series of rearrangements in order to share certain elements of the case that demonstrate motherhood as a place of indeterminacy and overlapping roles [daughter and mother], which allow for interpretations of the influences of being a daughter on the mothering of new mothers. In this work, we also propose a new look at the concept of reparation, which is associated with a maternal action aimed at appeasing a child's need not previously considered. The situations experienced during the research underscore the importance of specialized listening to mother-women and the use of brief psychotherapy psychoanalysis as a potential avenue for promoting insights capable of effecting certain changes in the dynamics of new mothers, thereby offering therapeutic benefits in reducing maternity-related discomfort symptoms. Furthermore, the theories developed and the authors studied contribute to a clinical theory of parenthood, encompassing and dissecting not only the unique psychic functioning that emerges upon entering motherhood, but also proposing a distinct psychological temporality specific to this phase of female life.